Strategic IT Management A Toolkit for Enterprise Architecture Management - Hanschke, Inge (Springer Berlin Heidelberg : Imprint: Springer, 2010)
For you as an IT manager, changes in business models and fast-paced innovation and product lifecycles pose a big challenge: you are required to anticipate the impact of future changes, and to make rapid decisions backed up by solid facts. To be successful you need an overall perspective of how business and IT interact. What you need is a toolkit, enabling you to manage the enterprise from a helicopter viewpoint while at the same time accommodating quite detailed aspects of processes, organization, and software lifecycles. Strategic IT management embraces all the processes required to analyze and document an enterprise's IT landscape. Based on the experience of many projects and long discussions with both customers and academic researchers, Inge Hanschke provides you with a comprehensive and practical toolkit for the strategic management of your IT landscape. She takes a holistic view on the management process and gives guidelines on how to establish, roll out, and maintain an enterprise IT landscape effectively. She shows you how to do it right first time - because often enough there's no second chance. She tells you how to tidy up a IT patchworks - the first step towards strategic management - and she gives you advice on how to implement changes and maintain the landscape over time. The book's structure reflects the patterns that exist in strategic IT management from strategic planning to actual implementation. The presentation uses many checklists, guidelines, and illustrations, which will help you to immediately apply the content. So, if you are a CIO, an IT manager, a business manager, or an IT consultant, this is the book from which you'll benefit in most daily work situations.